TRANSFORMASI KESENIAN TRADISIONAL ANGKLUNG SERED BALANDONGAN GRUP TUNGGAL JAYA DESA SUKALUYU KECAMATAN MANGUNREJA KABUPATEN TASIKMALAYA TAHUN 2010-2019 - Sari Asy-syifatani Purn (2019)
This research entitled "TRANSFORMATION OF TRADITIONAL ARTS ANGKLUNG SERED BALANDONGAN TUNGGAL JAYA GROUP SUKALUYU VILLAGE, MANGUNREJA, TASIKMALAYA in 2010-2019". The purpose of this research is to describe how the transformation that happened in traditional art angklung sered baladongan from 2010 to 2019. Along with the times, traditional art angklung sered baladongan had the transformation in the form of functions that are not followed up also transformed with both small scale and large scale. Large-scale transformation occurred in 2010 to 2019. This is a reason for researchers to get information about the transformation that occurred in the art of angklung sered balandongan from 2010 to 2019. The transformation that happened to this art, how to transform the process and change what happened in angklung art between the years 2010-2019. For this reason, the information obtained can be described properly, so the method used in this research is descriptive method by obtaining qualitative data so that the data presented in explanation, not numbers. The results obtained from this study are information found about the transformation that occurred, the transformation process, and the discovery of the reason for the transformation to angklung art in 2010-2019. Kata Kunci: Transformation, Traditional Art, Angklung, Angklung Sered Balandongan